THE MESSAGE OF RELIGIOUS MODERATION IN THE “KELEANG” TOMB PILGRIMAGE TRADITION (AN EXPECTACY VALUE COMMUNICATION APPROACH) - Ummah, Athik Hidayatul; Bustami, Yazid (Universitas Islam Negeri Mataram, 2024)
Tomb pilgrimage is one of the religious traditions of Indonesian (especially in Lombok). It is strongly lives in society with various unique local wisdom rituals. Even though the tradition of grave pilgrimages has a long history as an Islamic identity, controversy over the prohibition of grave pilgrimages still occurs. Like the controversial statement by Salafi-Wahabi leader Mizan Qudsiyah in a hate-speech case which were broadcast on a YouTube channel entitled religious tourism to cemeteries. One indicator of religious moderation which is a pillar of nationality and diversity in Indonesia is acceptance of tradition. This research aims to find and analyze the motives of the pilgrims and the meaning of the messages from each ritual procession for the pilgrimage to the Keleang Tomb. The Keleang Tomb Pilgrimage is unique because it accommodates religious and cultural elements. At the same time, there are sacred values that must be understood and implemented in accordance with the advice of religious and traditional leaders. This research also examines the values of religious moderation in the Keleang Tomb pilgrimage tradition. Local traditions have the power to build togetherness, unite communities and avoid poverty. This research method is qualitative with an interpretive phenomenological approach which emphasizes the experiences of pilgrims. This study uses a communication perspective because every traditional and religious ritual involves two communication models, namely intrapersonal and interpersonal. In communication theory, the expectacy value emphasizes that there are hopes and values or beliefs that influence people's behavior in continuing to make pilgrimages to the Kaleang Tomb. Pilgrimage to the Keleang Tomb is not only to ask (pray) to Allah, but also as a form of gratitude (salametan) for the good things obtained. While the cemetery acts as an intermediary (wasilah).